Thermal Interaction of Mobile Ground Systems with Boulders on the Lunar Surface - Joel Guetzlaff; Philipp Reiss; Markus Czupalla (Engineering Proceedings)
The paper at hand evaluates the necessity of depicting topographic features like boulders on the lunar environment in thermal analyses for a size of up to 6.5 m in diameter. The question regarding the thermal influence becomes relevant when analysing a technical system within the lunar environment. This influence on the thermal behaviour of a test object is investigated in sensitivity studies. It is shown that the local surroundings can significantly alter a system’s net heat flux and can lead to overheating or critically cooling down instead of theoretically surviving when not considering local topographic features. Especially for small and lightweight systems ≤20 kg, like micro rovers, the effect of the surrounding on the system’s temperature becomes critical due to the low thermal capacity. Thus, it is a substantial aspect to be accounted for during the design phase as well as in mission operation.